Van der Waals Emulsions: Emulsions Stabilized by Surface‐Inactive, Hydrophilic Particles via van der Waals Attraction. Issue 30 (20th June 2018) - Marina, Paula Facal; Cheng, Chongling; Sedev, Rossen; Stocco, Antonio; Binks, Bernard P.; Wang, Dayang
Abstract: Surface‐inactive, highly hydrophilic particles are utilized to effectively and reversibly stabilize oil‐in‐water emulsions. This is a result of attractive van der Waals forces between particles and oil droplets in water, which are sufficient to trap the particles in close proximity to oil–water interfaces when repulsive forces between particles and oil droplets are suppressed. The emulsifying efficiency of the highly hydrophilic particles is determined by van der Waals attraction between particle monolayer shells and oil droplets enclosed therein and is inversely proportional to the particle size, while their stabilizing efficiency is determined by van der Waals attraction between single particles and oil droplets, which is proportional to the particle size. This differentiation in mechanism between emulsification and stabilization will significantly advance our knowledge of emulsions, thus enabling better control and design of emulsion‐based technologies in practice. Abstract : Highly hydrophilic surface‐inactive particles can effectively and reversibly stabilize oil‐in‐water emulsions thanks to van der Waals attraction between particles and oil droplets in water, referred to as a van der Waals emulsion. In contrast to Pickering emulsions, these emulsions are vulnerable to external disturbance and subject to the dynamic exchange of different sized particles between oil and water phases.